Applications of Microbial Proteases: A Review - Fasiku, Samuel Adedayo; Afolabi, Femi Johnson; Odeyale, Christiana Ify (Darul Yasin Al Sys, 2026)
Microbial proteases have attracted increasing attention as eco-friendly biocatalysts because of their broad functional versatility and advantages over proteases derived from plants and animals. This review examines the major sources, classification, production methods, and sectoral applications of microbial proteases. Produced by bacteria, actinomycetes, and fungi, microbial proteases are classified according to optimum pH range, catalytic mechanism, and site of action, and are commonly generated through submerged and solid-state fermentation. The review shows that these enzymes have diverse industrial applications in detergent, leather and tanning, food and dairy, brewing and beverage processing, and textile production. In medical and pharmaceutical contexts, microbial proteases are applied in wound debridement and healing, antimicrobial and antibiofilm activities, drug development, diagnostics, and therapeutic interventions. In agriculture, they support animal feed supplementation by improving protein digestion and function as biological control agents by disrupting pathogen attachment, penetration, and colonization of plant tissues. In the environmental sector, their applications include waste management, bioremediation, and the recycling of keratinous and other protein-rich wastes. Overall, this review underscores the wide-ranging utility of microbial proteases across industrial, medical, agricultural, and environmental sectors, highlighting their potential as sustainable biological agents for diverse biotechnological applications.